Effects of concentration, distance, and application methods of Altriset (Chlorantraniliprole) on eastern subterranean termite (Isoptera: Rhinotermitidae). (12th June 2014) - Barwary, Znar; Gorzlancyk, Austin; Hu, Xing Ping
Abstract The effects of various concentrations, distance, and application methods of Altriset (Chlorantraniliprole) were investigated against one of the most destructive termites, the eastern subterranean termite, Reticulitermes flavipes Kollar. Three laboratory experiments were conducted. First, we examined the concentration effect of treating the soil contiguously to established foraging tunnels at a fixed 1 m distance. The results demonstrated 100% termite control in 19 d posttreatment at 100 and 50 μg/g and 27% termite mortality at 25 μg/g. Second, we tested the distance effect of the soil treatment (2 and 4 m) on the efficacy of Altriset to the satellite termite populations at a fixed 50 μg/g concentration. This resulted in 100% termite control in 22 d posttreatment at both 2 and 4 m. Third, we examined the effect of differing application methods using 12.5 and 25 μg/g prior to the establishment of foraging tunnels at a fixed 1m distance. This illustrated 100% termite control in 9 d posttreatment at 25 μg/g and 12 d posttreatment at 12.5 μg/g. The third experiment demonstrated soil treatments that were applied prior to termite tunnel establishment had greater efficacy than applications made post tunnel construction. Our results provide a comprehensive understanding about the efficacy of Altriset treatments on eastern subterranean termites.